THE EFFECT OF FEEDING LEVEL OF B-6 CELLULOLYTIC BACTERIA PROBIOTIC ADMINISTERED THROUGH DRINKING WATER ON THE EGG PRODUCTION OF LOHMANN BROWN HEN 40 - 48 WEEK OLD - I G. R., Wedana; Bidura, I G. N. G.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika, 2018)
The aim of this research is to study the effect of B-6 cellulolytic bacteria probiotic through drinking water on the 40-48 week old Lohmann Brown hen egg production 40-48 weeks old. The research was conducted in Dajan Peken Village, Tabanan, Bali, for three months starting from preparation until report writing. The design used in this study was Completely Randomized Design (RAL) with three treatments and six replications. The treatments were: drinking water without probiotic addition of B-6 cellulolytic bacteria as control (P0), drinking water with probiotics of B-6 cellulolytic bacteria as much as 0.2% (P1), and drinking water with B- 6 probiotic of cellulolytic bacteria with 0.4% (P2). The variables observed in this study were ration consumption, drinking water consumption, egg number, total egg weight, average egg weight and Feed Conversion Ratio (FCR). The results showed that the consumption of rations, drinking water, total eggs, total egg weight and average egg weight at treatment of P1 and P2 were significantly higher (P <0.05) compared with P0 treatment while the FCR has decrease. Based on the results, it can be concluded that the provision of B-6 cellulolytic bacteria as a source of probiotics through drinking water at the level of 0.2% and 0.4% can increase the 40-48 week old Lohmann Brown hen egg production and decrease FCR.   Keywords: Probiotics of B-6 Cellulolytic Bacteria, Consumption, Lohmann Brown hen, Egg Production